2017
DOI: 10.1056/nejmoa1710030
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan in Later-Stage Autosomal Dominant Polycystic Kidney Disease

Abstract: BACKGROUNDIn a previous trial involving patients with early autosomal dominant polycystic kidney disease (ADPKD; estimated creatinine clearance, ≥60 ml per minute), the vasopressin V 2 -receptor antagonist tolvaptan slowed the growth in total kidney volume and the decline in the estimated glomerular filtration rate (GFR) but also caused more elevations in aminotransferase and bilirubin levels. The efficacy and safety of tolvaptan in patients with later-stage ADPKD are unknown. METHODSWe conducted a phase 3, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
479
4
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 470 publications
(522 citation statements)
references
References 33 publications
24
479
4
15
Order By: Relevance
“…The results of this prospective double blinded, placebo-controlled trial, which included 1495 subjects, have been published recently. 34 In patients with later stage ADPKD, the use of tolvaptan was associated with a slower eGFR decline (-2.34 mL/mn/1.73 m 2 versus -3.6 mL/mn/1.73 m 2 ). These results suggest that tolvaptan may be effective over a broad range of CKD stage.…”
Section: Reprise Trialmentioning
confidence: 89%
See 3 more Smart Citations
“…The results of this prospective double blinded, placebo-controlled trial, which included 1495 subjects, have been published recently. 34 In patients with later stage ADPKD, the use of tolvaptan was associated with a slower eGFR decline (-2.34 mL/mn/1.73 m 2 versus -3.6 mL/mn/1.73 m 2 ). These results suggest that tolvaptan may be effective over a broad range of CKD stage.…”
Section: Reprise Trialmentioning
confidence: 89%
“…34,35 In TEMPO 3:4, uricemia increased and some patients had gout attacks. A reversible GFR reduction was observed in the first 2 weeks of treatment.…”
Section: Transient Extracellular Fluid Volume Contractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Torres et al [72] showed that tolvaptan retarded the increase in total kidney volume and slowed the progression of kidney disease in patients with ADPKD, but it was associated with high aquaresis-related adverse effects and higher discontinuation rates. Moreover, in a more recent study, tolvaptan slowed the decline in kidney function in patients with later-stage ADPKD [73]. Gansevoort et al [74] showed that tolvaptan decreased albuminuria without affecting blood pressure in patients with ADPKD.…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%